Evaluation of Newborns with Non-COVID-19 Pneumonia Hospitalized in the Neonatal Intensive Care Unit during the COVID-19 Pandemic, Turkey, Izmir 2020–2021 - Soysal, Buse; Özdemir, Senem Alkan; Gönüllü, Ahmet; Kalkanlı, Oğuz Han; Ayhan, Fahri Yüce; Çalkavur, Şebnem; Yıldırım, Tülin Gökmen (Journal of Pediatric Infectious Diseases, 2022)
Objective In this study, we aimed to compare the clinical, laboratory, and radiological findings of noncoronavirus disease 2019 (COVID-19) viral agents in newborn infants hospitalized for lower respiratory tract infection during the COVID-19 pandemic.Methods This prospective cross-sectional study conducted between 11 March 2020 and 31 July 2021 included neonates with lower respiratory tract infections admitted to the neonatal intensive care unit of the Dr. Behcet Uz Children's Hospital. Nasopharyngeal swab samples were taken from all hospitalized patients for multiplex respiratory polymerase chain reaction (PCR) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) PCR. The detection of respiratory viral pathogens was performed by multiplex real-time PCR assay (Bosphore Respiratory Pathogens Panel Kit V4, Anatolia Geneworks, Turkey). Infants with SARS-CoV-2 PCR positivity were excluded from the study. Patients' data were obtained from the electronic medical registry system. The non-COVID-19 viruses of the cases were analyzed according to seasonal variation (in/off-season). The pulmonary findings of the cases were classified as normal, infiltration, air bronchogram, and reticulogranular appearance at the time of admission.Results A total of 80 infants were included during the study period. A multiplex PCR test was performed to identify viral agents affecting the lower respiratory tract of infants; it was determined that 31% (25 out of 80) were respiratory syncytial virus (RSV), 41% (33 out of 80) were rhinovirus (Rhino), and the remaining portion (28%, 22 out of 80) were other viral agents (enterovirus, bocavirus, adenovirus, influenza, and parainfluenza). Compared with Rhino and other viral agents, RSV was detected most frequently in seasonal hospitalizations (p < 0.05). When chest radiography and laboratory findings were evaluated, the rate of “infiltration” /“lymphopenia” was significantly associated with infants with RSV lower respiratory tract infections (p < 0.05).Conclusion During the pandemic period, RSV affected the prognosis in intensive care unit admissions due to lower respiratory tract infection in newborns.
Keywords: neonate; respiratory syncytial virus; lymphopenia; chest X-ray